Elementary Technical Mathematics

Published by Brooks Cole
ISBN 10: 1285199197
ISBN 13: 978-1-28519-919-1

Chapter 6 - Section 6.3 - Equations with Parentheses - Exercises: 29

Answer

x=-1

Work Step by Step

Simplifying 3(x + 4) + 3x = 6 Reorder the terms: 3(4 + x) + 3x = 6 (4 * 3 + x * 3) + 3x = 6 (12 + 3x) + 3x = 6 Combine like terms: 3x + 3x = 6x 12 + 6x = 6 Solving 12 + 6x = 6 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + 6x = 6 + -12 Combine like terms: 12 + -12 = 0 0 + 6x = 6 + -12 6x = 6 + -12 Combine like terms: 6 + -12 = -6 6x = -6 Divide each side by '6'. x = -1 Simplifying x = -1
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.